Candidate selective sweeps in US wheat populations - Sajal R. Sthapit; Travis M. Ruff; Marcus A. Hooker; Bosen Zhang; Xianran Li; Deven R. See (The Plant Genome)
Abstract Exploration of novel alleles from ex situ collection is still limited in modern plant breeding as these alleles exist in genetic backgrounds of landraces that are not adapted to modern production environments. The practice of backcross breeding results in preservation of the adapted background of elite parents but leaves little room for novel alleles from landraces to be incorporated. Selection of adaptation‐associated linkage blocks instead of the entire adapted background may allow breeders to incorporate more of the landrace's genetic background and to observe and evaluate novel alleles. Important adaptation‐associated linkage blocks would have been selected over multiple cycles of breeding and hence are likely to exhibit signatures of positive selection or selective sweeps. We conducted genome‐wide scan for candidate selective sweeps (CSS) using Fst, Rsb, and xpEHH in state, regional, spring, winter, and market‐class population pairs and reported 446 CSS in 19 population pairs over time and 1033 CSS in 44 population pairs across geography and class. Further validation of these CSS in specific breeding programs may lead to identification of sets of loci that can be selected to restore population‐specific adaptation in pre‐breeding germplasms.